(untitled) (Scientific journal of the Fergana State University, 2024)
This article explores the semantic peculiarities of proverbs related to health and sickness in English and Uzbek cultures. By employing different methodologies the article provides a comprehensive examination of how these proverbs reflect and shape cultural attitudes toward well-being and illness. Through detailed comparisons, the article highlights both the universal themes and the unique cultural expressions found in the proverbs of these two languages. It delves into the linguistic structures, cultural contexts, and thematic elements of proverbs, uncovering insights into the collective wisdom and societal values embedded within them. This analysis not only enhances the understanding of proverbs as a form of cultural expression but also offers a valuable perspective on the interconnectedness of language, health, and culture.